Choice of Intra-arterial Therapy for Hepatocellular Carcinoma: Evidence and Future Horizons - Ghani, Mansur A.; Thakur, Vinayak; Geschwind, Jean-François (Digestive Disease Interventions, 2017)
Hepatocellular carcinoma is the second most common cause of cancer-related deaths worldwide. Along with viral and alcoholic hepatitis, obesity is the leading cause for increasing incidence in the western world, specifically in the United States. As most patients initially present with intermediate to advanced stage disease, curative therapies such as ablation, surgical resection, or liver transplantation cannot usually be applied. Thus, intra-arterial therapies (IATs), such as transarterial chemoembolization (TACE), have become a mainstay of treatment. Several variations of transarterial embolotherapy, such as bland transarterial embolization or drug-eluting bead TACE, are currently available and used in clinical practice. Yttrium-90 radioembolization is a distinct IAT that relies on delivery of radiation to surrounding tissue for tumor death. However, no clear guidelines or evidence exist that would favor one of these options over the other, leaving the decision-making process open to influence by local expertise and experience. In addition, combining TACE with systemic antiangiogenic agents, such as the multityrosine kinase inhibitor sorafenib, has been investigated in several prospective clinical trials without clearly demonstrating substantial survival benefits of the combination over TACE alone. This review will summarize and discuss the available clinical evidence and indications for each treatment modality with the goal of facilitating clinical decision-making processes, and provide an overview of the ongoing efforts to compare different IAT modalities.
Keywords: intra-arterial therapy; HCC; cTACE; TAE; DEB-TACE